Translation – The fifth language skill? A comparison of the role of translation in Finnish lukio and the International Baccalaureate Diploma Programme - Hurd, Emily (fi=Turun yliopisto|en=University of Turku|, 2017)
This study attempts to answer the question “Should translation be considered a fifth language skill?” by examining and comparing the use of translation as a language learning and assessment method in the national Finnish lukio curriculum and the curriculum of the International Baccalaureate Diploma Programme (IBDP). Furthermore, the students’ ability to translate and their opinions on the usefulness of translation in language learning will be examined. The students’ opinions were gathered through a questionnaire that was given to 156 students studying in either lukio or the IBDP in Turku and Rovaniemi. I present and compare the role of translation in selected language teaching and learning methods and approaches, and discuss the effectiveness of translation as a language learning method and an assessment method. The theoretical discussion provides the basis for examining the role of translation as a language learning method and an assessment method in the curricula and final examinations of both education programs. The analysis of the two curricula indicated that there is a significant difference in the use of translation, as translation is used as a language learning method and as an assessment method in lukio, but is not used in either form in the IB. The data obtained through the questionnaire indicated that there is a difference in the level of language competence between the lukio and IB students and suggested that the curriculum in which the student studies has some effect on his/her cognitive use of translation, ability to translate and opinions concerning the usefulness of translation in language learning. The results indicated that both groups of students used translation, along with their mother tongue, as a cognitive language learning method, and, contrary to the expectations set by the analysis of the two curricula, the IB students performed better in the translation exercises than lukio students. Both groups of students agreed that translation is a useful language learning method, and indicated that the most common dictionaries they use are bilingual Internet dictionaries. The results suggest that translation is a specific skill that requires teaching and practice, and that perhaps the translation exercises used in lukio should be developed from translating individual words and phrases to translating cultural elements. In addition, the results suggest that perhaps the IB curriculum should include the use of translation exercises (e.g., communicative translation exercises) in order to help students learn to mediate between languages and cultures rather than learn languages in isolation from each other.